Sistem Informasi Pengelolaan Travel Agent Berbasis Website - Sri Rahayu Ginantra, Ni Luh Wiwik; Penanta, Aditya (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Travel agent is a company engaged in the travel agency. Business management processes such as making sales invoices that still use the handwriting method along with sales and purchase reports that are still used Microsoft Excel. Travel agent requires a website-based system where the management of its business to be more effective , safe and accessible anywhere and anytime. In the design phase Data Flow Diagram notation is used, Conceptual Data Models, Physical Data Models and Mockups. The development of the system uses Sublime Text 3 and SQLyog as a Database Management System and is tested using blackbox testing. The results have successfully built an information system for managing a travel agent where the system was built aimed at helping the business management process of Travel agent to be faster, neater, avoid the risk of losing and unnecessary errors.